2000
DOI: 10.1080/00498250010021684
|View full text |Cite
|
Sign up to set email alerts
|

Determining the best animal model for human cytochrome P450 activities: a comparison of mouse, rat, rabbit, dog, micropig, monkey and man

Abstract: 1. In the present study, nine cytochrome P450 enzyme activities in seven species were characterized to allow a practical means of comparing this important metabolic step between various test animals and man. 2. Enzyme activities and kinetic parameters were first determined towards marker substrates for human cytochrome P450 enzymes. Inhibition profiles were then determined with both antibodies directed against various cytochrome P450 enzymes and with chemical inhibitors. 3. Both the enzyme kinetic parameters/e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
258
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(295 citation statements)
references
References 30 publications
26
258
3
1
Order By: Relevance
“…Monkeys were originally considered to have pharmacokinetic properties similar to those of humans due to genetic similarities, however, previous studies showed that the bioavailability (BA) of some drugs including human CYP3A substrates was markedly lower in monkeys than in humans [7,[15][16][17][18][19][20]. Monkeys have also been shown to exhibit higher CYP activities for human CYP2D6 substrates in their liver microsomes than humans [10,12,16,21,22]. Pigs and minipigs are increasingly being used in pharmacokinetic and toxicity studies, because their metabolism has been subjected to further research and has recently attracted considerable attention [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monkeys were originally considered to have pharmacokinetic properties similar to those of humans due to genetic similarities, however, previous studies showed that the bioavailability (BA) of some drugs including human CYP3A substrates was markedly lower in monkeys than in humans [7,[15][16][17][18][19][20]. Monkeys have also been shown to exhibit higher CYP activities for human CYP2D6 substrates in their liver microsomes than humans [10,12,16,21,22]. Pigs and minipigs are increasingly being used in pharmacokinetic and toxicity studies, because their metabolism has been subjected to further research and has recently attracted considerable attention [23].…”
Section: Introductionmentioning
confidence: 99%
“…Humans and rodents, such as mice and rats, generally exhibit greater species differences in CYP activities; however, rodents have frequently been used as animal models in drug discovery [4][5][6][7][8][9][10][11]. On the other hand, Bogaards et al [12] reported that CYP1A activity in mouse microsomes and CYP3A activity in mouse and rat microsomes were similar to those in human microsomes [12]. Although dogs are frequently used as non-rodent species in nonclinical studies, information concerning the canine CYP system is more limited.…”
Section: Introductionmentioning
confidence: 99%
“…MROD and EROD are used as marker activities for CYP1A not only in human and rat, but also in several other species [6,9,51]. The CYP substrates used in this study were also successfully used in our previous study, where in vitro activities of biotransformation enzymes in pig, cattle, goat and sheep were measured [46].…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of the sequence of canine isoforms with homologues of other species have shown a high degree of amino acid sequence identity, (6) but the similarities in sequence have not always predicted similarities in enzymatic characteristics. In an effort to better understand the metabolic profile of the canine CYP450s, numerous studies have been conducted comparing the activity and specificity of dog CYP450 isozymes with those of other species (6,8,56,59). An overarching conclusion in many of these studies is that there are significant differences in the metabolic activities of dog CYP450s when compared with other species.…”
Section: Hepatic Metabolismmentioning
confidence: 99%